2012
DOI: 10.1111/j.1745-4530.2012.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

MODELING OF THE ADHESION OF BACILLUS CEREUS ISOLATED FROM A DAIRY PLANT AS A FUNCTION OF TIME AND TEMPERATURE

Abstract: Adhesion of Bacillus cereus to stainless steel 304 #4 was evaluated after different times and temperatures of contact. Mathematical model was obtained, which was capable of predicting the adhesion of B. cereus to stainless steel as a function of temperature (4-35C) and time (1-10 days). The increase in temperature from 4 to 35C resulted in an increased number of B. cereus cells attached more than 3 log cycles for an adhesion time of 1 day and more than 4 log cycles for an adhesion time of 10 days, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The coupling of diafiltration with nanofiltration caused a decrease in the content of monovalent elements (Na, K), and in that of the microelement Zn. Such an effect of diafiltration used for acid whey concentration was also reported by ROMAN et al (2009ROMAN et al ( , 2012. Bioavailability of dietary supplements, including minerals, can be defined as the proportion of the administered substance capable of being absorbed and available for use or storage (SRINIVASAN 2001).…”
Section: Resultssupporting
confidence: 54%
“…The coupling of diafiltration with nanofiltration caused a decrease in the content of monovalent elements (Na, K), and in that of the microelement Zn. Such an effect of diafiltration used for acid whey concentration was also reported by ROMAN et al (2009ROMAN et al ( , 2012. Bioavailability of dietary supplements, including minerals, can be defined as the proportion of the administered substance capable of being absorbed and available for use or storage (SRINIVASAN 2001).…”
Section: Resultssupporting
confidence: 54%
“…For the μmax , λ, and viable counts assays, statistical analysis were performed to determine significant differences ( p ≤ 0.05) using analysis of variance (ANOVA) followed by Tukey’s test or Student’s t -test. The results of μmax from turbidity assays were analyzed using response surface methodology (RSM) and the goodness-of-fit and statistical validity of the models generated by RSM were assessed by using one-factor ANOVA, as well as by providing the adjusted determination coefficient ( R 2 adj) and the statistical significance of the regression models ( p -value 0.05) ( Bernardes et al, 2012 ). All analyses were performed using the Statistica software version 7.0 (StatSoft, Inc., Tulsa, OK, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Studies that used mathematical models to verify the behavior of biofilm formation generally find relative deviation higher than that found in our study. Bernardes et al () found relative deviation from −11.47 to 38.25%. Peña et al () obtained a relative deviation from −19.35 to 15.48% and from −100 to 20% for two different experiments (model with an initial inoculum of 6 log cfu/ml and model with an initial inoculum of 3 log cfu/ml, respectively).…”
Section: Resultsmentioning
confidence: 96%
“…Studies that used mathematical models to verify the behavior of biofilm formation generally find relative deviation higher than that found in our study. Bernardes et al (2013) found relative deviation from 211.47 to 38.25%. Peña et al…”
Section: Modeling Of Adhesion and Biofilm Formationmentioning
confidence: 91%